Basic guide to orthodontic dental nursing - Grist, Fiona (Chichester, West Sussex : Blackwell Pub., 2010)
'The Basic Guide to Orthodontic Dental Nursing is a must-have introduction for those seeking to develop their knowledge and understanding of this core area of clinical practice. Written in a clear and accessible format, with colour illustration throughout, the book is a guide for all dental nurses with an interest in orthodontics. It is designed to reflect sections of the syllabus of the Certificate in Orthodontic Dental Nursing. Chapters cover such key topics as tooth eruption patterns, removable and fixed appliances, de-bonding, and retention. There are also sections on care prior to treatment, including the requirements for a first appointment, and there is helpful guidance on maintaining motivation - particularly for young patients and their parents. Published in a compact format for portability and easy reference, this is a valuable addition to the Basic Guides series'--Provided by publisher
Keywords: Orthodontics; Dental Assistants